A proteção integral e o egresso da medida socioeducativa de internação na perspectiva de reinserção social - Lima, Marilia Cerqueira (2018)
The central theme of this study is the coverage of full protection and the analysis of necessary public policies, their strategies, mechanisms and instruments of action and its respective responsibility relationship to the promotion of adolescents’ rescue conflicting with the Law and their posterior social-familiar reinsertion, as an egress of internment social-educative measure. Therefore, this work stems from, initially, the investigation of a child’s and adolescent’s social trajectory, the influences and determinations of social inequality relationships and its respective juridical-social support from the protection special system. Henceforth, there is the compliance of the special custody as an expression of collateral for this full protection and absolute priority, guided by the right to freedom, equality, social inclusion, non-discrimination, proper legal process and human dignity. Considering the insertion of this juvenile in the System of Assurance of Child and Adolescent Rights, the infractional act, the social-educative measures – notably the internment one, the service policy, the socio-educational process and the egress condition, the objective becomes the framework of needed social protection, under the form of a special attention network, as an emancipatory condition, capable of conducting him or her to the respective rehabilitation. Diverse bibliographic and documental researches were used, besides the indication of data as situational milestones of national reality and, specially, of the State of Alagoas, for analysis and formulation of challenges and action strategies before confront policies